Effects of Functional Group Position on Hole Transporting Properties of Carbazole Derivatives in Perovskite Solar Cells (Communications in Computational Chemistry, 2022)
Several carbazole derivatives (V866, V867 and V868) as hole transportingmaterials (HTMs) in perovskite solar cells are designed to explore the functional groupposition effect on electrochemical properties. The material properties are studied on thefirst-principle calculations combined with the Marcus theory. The results illustrate thatV866 (ortho-position) has the suitable HOMO energy level matched with the metalelectrode (-5.1 eV) and the perovskite absorption layer (-5.4 eV). Moreover, themolecular planarity of HTMs with the ortho-position functional groups is improved,which enhances intermolecular face-to-face $π-π$ stacking degree. Compared to V867and V868, the largest hole mobility value (0.007 ${\rm cm}^2 {\rm V}^{-1} {\rm s}^{-1})$ of V866 is obtained due to itsmodified molecular planarity. Therefore, V866 (ortho-position) is indeed an excellentcarbazole HTM. Our theoretical investigation of HTMs is helpful for understanding thehole transporting behaviors and developing higher performance HTMs.